2006
DOI: 10.1007/s00520-006-0041-x
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF mobilised granulocyte transfusions in 32 paediatric patients with neutropenic sepsis

Abstract: In contrast to the non-survivors, we observed a significant decrease in the C-reactive protein levels shortly after initiation of the GTX treatment in the surviving patients. A clear-cut benefit of GTX for children with neutropenic sepsis cannot be concluded from these data, but in children with (severe) bacterial sepsis refractory to antibiotic treatment, GTX were feasible, safe and could reduce mortality rates in this subgroup of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 25 publications
4
44
0
1
Order By: Relevance
“…17 Recent studies of therapeutic granulocyte transfusions for neutropenic infections in patients with leukemia and/or undergoing HSCT have shown survival rates of 31-81%; in patients with invasive fungal infections, the survival rates range from 20-80%. These studies, summarized in Table 4, [1][2][3][4][5][6][18][19][20][21][22][23][24][25] vary in the definition of invasive fungal infections, the timing of initiating granulocyte therapy, the cell dose of granulocytes transfused, and the number of granulocyte doses given. One study was randomized, but only 60% of patients were actually neutropenic prior to receiving granulocytes, and 44% of patients randomized to the granulocyte arm received only one or two transfusions before neutrophil recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Recent studies of therapeutic granulocyte transfusions for neutropenic infections in patients with leukemia and/or undergoing HSCT have shown survival rates of 31-81%; in patients with invasive fungal infections, the survival rates range from 20-80%. These studies, summarized in Table 4, [1][2][3][4][5][6][18][19][20][21][22][23][24][25] vary in the definition of invasive fungal infections, the timing of initiating granulocyte therapy, the cell dose of granulocytes transfused, and the number of granulocyte doses given. One study was randomized, but only 60% of patients were actually neutropenic prior to receiving granulocytes, and 44% of patients randomized to the granulocyte arm received only one or two transfusions before neutrophil recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Large studies of granulocyte transfusions in the era of granulocyte colony-stimulating factor (G-CSF) use [1][2][3][4][5][6] have generally focused on neutropenic patients with acute leukemia and/or on patients undergoing hematopoietic stem cell transplantation (HSCT). Infections, especially those caused by invasive fungi, are a major cause of death in patients with severe aplastic anemia (SAA).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on the use of recombinant G-CSF to mobilize bone-marrow granulocytes to the blood pool in granulocyte donors have provided encouraging results. [2][3][4][5][6][7][8][9][10] So far the most efficient way to increase the level of neutrophils is to administer a single dose of G-CSF plus corticosteroids 11 to increase the granulocyte yield 5-to 10-fold higher than a decade ago; this ensures a good therapeutic dose of granulocytes for transfusion. To provide effective therapy, not only must the numbers of granulocytes be sufficient, but the cells must also retain full functional capacity.…”
Section: Introductionmentioning
confidence: 99%
“…21 Renewed interest in this therapy arose with the introduction of granulocyte colonystimulating factor (G-CSF) and the possibility of greatly increasing the dose of granulocytes transfused by administering G-CSF to healthy granulocyte donors. Studies over the last 20 years have shown that 3 to 4 times as many granulocytes can be collected from donors stimulated with G-CSF (with or without the addition of corticosteroids), [22][23][24][25][26][27][28][29][30][31][32][33][34] that these collected cells circulate in neutropenic recipients, 23,26,28 and that the cells appear to function normally as judged by both in vitro and in vivo testing. 28,35,36 The evidence for clinical efficacy of high-dose granulocyte transfusion therapy has been elusive.…”
Section: Introductionmentioning
confidence: 99%